Distribution of antiretroviral therapy through private pharmacies and postal courier services during COVID‐19 in Botswana: acceptability and reach of two out‐of‐facility individual differentiated service delivery models. (28th October 2021) - Mpofu, Mulamuli; Moyo, Tackler; Gilbert, Masego; Dikobe, Wame; Nishimoto, Lirica; Katiko, Gorata; Batuka, James; Satti, Hind; Qambayot, Maria; Mahler, Hally; Kitso, Lesego; Marqusee, Hannah; et al.
Abstract: Introduction: The advent of COVID‐19 has put pressure on health systems as they implement measures to reduce the risk of transmission to people living with HIV (PLHIV) and healthcare workers. For two out‐of‐facility individual differentiated service delivery (DSD) models, we assessed acceptability of antiretroviral therapy (ART) distribution through private pharmacies and reach of home delivery of ART through courier services during the COVID‐19 pandemic in Botswana. Methods: From 24 July to 24 August 2020, we conducted exit interviews with PLHIV receiving ART from 10 high‐volume public facilities in Gaborone, and mapped and conducted an online survey with private pharmacies to assess willingness and capacity to dispense ART to PLHIV enrolled in the Botswana national ART program. We piloted ART home delivery from September 2020 to January 2021 in Gaborone and Kweneng East districts for PLHIV accessing ART at two Tebelopele Wellness Clinics. We used cascade analysis to measure the enrolment and eventual reach (percentage of those reached amongst those who are eligible) of ART home delivery. Results: Sixty‐one PLHIV and 42 private pharmacies participated. Of the PLHIV interviewed, 37 (61%) indicated willingness to access ART from private pharmacies and pay BWP50 (∼US4) per refill for a maximum of two refills per year. All private pharmacies surveyed were willing to provide ART, and 26 (62%) would charge a dispensing fee (range = BWP50–100; ∼US4–8) per refill. All pharmacies operated 12 h/day, 6 days/week and on public holidays. In the home delivery pilot, 650 PLHIV were due for refills, 69.5% ( n = 452) of whom were eligible for home delivery. Of these, 361 were successfully offered home delivery and 303 enrolled (enrolment = 83.9%: female = 87.2%, male = 77.8%, p = 0.013). A total of 276 deliveries were made, a reach of 61%. Conclusions: Providing ART through private pharmacies and home delivery was acceptable in Botswana during COVID‐19. Surveyed pharmacies were willing and able to dispense ART to PLHIV attending public sector facilities for free or for a nominal fee. Additionally, using courier services for ART home delivery is a novel and viable model in countries with a reliable courier service like Botswana and should be scaled up, particularly in urban areas.